Evidence for oxidative stress in unstable angina. Issue 11 (November 1992) - McMurray, John; Chopra, Mridula; Abdullah, Ibrahim; Smith, W Ewen; Dargie, Henry J
Abstract : Objective —To determine whether unstable angina, which is characterised by recurring episodes of myocardial ischaemia and reperfusion, is associated with oxidative stress (that is, where there is an imbalance between oxidants, such as free radicals, which are in excess and antioxidants). Design —Between group comparison of patients with unstable angina, stable angina, and healthy controls. Setting —The coronary care unit and cardiac investigation ward of a regional cardiology centre. Patients —Twenty five consecutive patients admitted to the coronary care unit with unstable angina. Twenty five consecutive patients admitted to the cardiac investigation ward (patients with stable angina undergoing coronary angiography) were used as control for the presence of [ill], drug treatment, and smoking habit. Thirty eight healthy controls (hospital staff and patients admitted for minor surgical procedures who were otherwise healthy) were also studied. Main outcome measures —Thiobarbituric acid related substances (TBARS) in plasma and plasma reduced thiol (PSH) as indicators of oxidative damage to lipids and proteins respectively were measured. Coronary angiography was performed in all patients with stable angina and roughly half of those with unstable angina. Results —Mean (SEM) plasma TBARS in unstable angina and stable angina were 9·95 (0·36) nmol/ml and 9·14 (0·28) nmol/ml respectively (p = 0·08). Mean plasma TBARS in healthy controls were 8·09 (0·21) nmol/ml (p < 0·05 compared with both angina groups). Mean (SEM) PSH concentration in unstable angina was 4·21 (9) nmol/ml and in stable angina was 4·85 (9) nmol/ml (p < 0·05). Mean PSH in healthy controls was 5·64 (8) nmol/ml (p < 0·001 compared with both angina groups). The extent of coronary artery disease, use of medication, and smoking habit were not significantly different between the angina groups. Conclusions —Biochemical indicators of oxidative stress are more abnormal in unstable than stable angina. This is in keeping with experimental evidence that episodes of ischaemia and reperfusion lead to generation of free radicals and toxic oxygen species and depression of endogenous antioxidant activity. The clinical significance of this finding remains to be determined, although, experimentally, free radicals and toxic oxygen species have adverse effects on myocardial contractile function, myocardial electrical stability, endothelial mediated vasodilatation, and coagulation.